Government Support and Investors Participation in Rwanda Stock Exchange - Alain, Amani Manzi; Faustin, Gasheja; Isaïe, KadhafiMisango (MultiTech Publisher, 2024)
This study was primarily motivated to investigate the investors participation as it has been observed to be low. The empirical examination was achieved through the variables of capacity building and enabling environment by government as independent variable and investors participation as dependent variable on the Rwanda Stock Exchange. The study included an explanatory and survey design. A total of 188 responses were received from a pool of 219respondents from RSE investors. This study's respondents were identified via purposive sampling, and responses were elicited using a 5-point Likert survey questionnaire. Data were collected through a number of ways, including a structured questionnaire for investors, semi-directed interviews with brokers, and a documentary review. According to the findings, investors' participation in the Rwanda Stock Exchange is primarily determined by their numeracy skills. On the whole, the combinations of these two determinants’ accounts for investor involvement on the stock exchange. The study discovered that both capacity building and enabling environment positively and significantly influenced investor participation in the Rwanda stock exchange. This study helps to make policy by demonstrating that financial education and literacy training (capacity building) should be provided to investors and prospective investors on the Stock Exchange. The government should continue to fine tune its legislation to encourage both local and international investors. The current article contributes to Rwanda stock exchange policy advisory as it has shown the benefit of capacity building and provision of enabling environment by government. The study can be a good library for researcher too.